Poverty Reduction and Economic Development: Evidence from a Systematic Literature Review - Sabri Sabri; Riza Novelda; Nasfi Nasfi; Suhatman Suhatman (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - This article examines the relationship between poverty reduction and economic development through a systematic literature review. The topic is important because economic development does not always reduce poverty evenly across different contexts. Design/methodology/approach - This study used a Systematic Literature Review guided by the PRISMA framework. Articles were collected from the Directory of Open Access Journals and limited to publications from 2022 to 2026. Of 230 records identified, 18 studies were selected after screening and eligibility assessment. Findings/Results - The review shows that economic development generally supports poverty reduction, but the effect is not automatic or uniform. Income inequality weakens the poverty-reducing effect of growth, while inclusive growth, fiscal policy, social assistance, human development, employment, infrastructure, and financial inclusion strengthen welfare improvement. Originality/Value - This study highlights poverty reduction as a multidimensional outcome shaped by growth, distribution, institutions, and social capability. The main implication is that inclusive and context-sensitive development strategies are needed to achieve more equitable and sustainable outcomes.